2008
DOI: 10.1161/atvbaha.107.158030
|View full text |Cite
|
Sign up to set email alerts
|

SM16, an Orally Active TGF-β Type I Receptor Inhibitor Prevents Myofibroblast Induction and Vascular Fibrosis in the Rat Carotid Injury Model

Abstract: Objective-TGF-␤ plays a significant role in vascular injury-induced stenosis. This study evaluates the efficacy of a novel, small molecule inhibitor of ALK5/ALK4 kinase, in the rat carotid injury model of vascular fibrosis. Methods and Results-The small molecule, SM16, was shown to bind with high affinity to ALK5 kinase ATP binding site using a competitive binding assay and biacore analysis. SM16 blocked TGF-␤ and activin-induced Smad2/3 phosphorylation and TGF-␤-induced plasminogen activator inhibitor (PAI)-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 48 publications
(62 reference statements)
0
49
1
Order By: Relevance
“…TGFb inhibitors have been used successfully in wound injury and tumor models to reverse TGFb-induced fibrosis, vessel density, tumor vascularity, and angiogenesis (41,42). Remodeling of the tumor vasculature could increase oxygen delivery to the tumor by reversing tumor-directed neoangiogenic vasculature.…”
Section: Resultsmentioning
confidence: 99%
“…TGFb inhibitors have been used successfully in wound injury and tumor models to reverse TGFb-induced fibrosis, vessel density, tumor vascularity, and angiogenesis (41,42). Remodeling of the tumor vasculature could increase oxygen delivery to the tumor by reversing tumor-directed neoangiogenic vasculature.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in several studies that the TGF-b system contributes to neointimal proliferation and that neointimal hyperplasia could be suppressed by using TGF-b antibody. 25,26 TGF-b1 is overexpressed in fibroproliferative vascular lesions, allowing a slow but uncontrolled growth while overproducing extracellular matrix components. In addition, Saura and coworkers 27 showed that endothelial cells treated with an NO donor exhibited a decreased response to TGF-b, resulting in a downregulation of TGF-b target genes.…”
Section: Discussionmentioning
confidence: 99%
“…SM16, a small kinase inhibitor of activin receptor-like kinase (ALK)5/ALK4, inhibits TGF-b signaling, prevents activation of receptor Smads (2/3) and reduces development of fibrosis in blood vessel walls and in the lungs. 62 As mentioned earlier, another promising target is the angiotensin II receptor, for which safe and selective blockers are available for oral treatment of hypertension. 54 The tumor stroma regulates invasion and metastasis Clinical and experimental data support the hypothesis that the tumor stroma regulates invasion and metastasis.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%